HACE1 as a bridge between oxidative stress and autophagy - Xia, Jiyue; Jiang, Youhong; Xin, Xiangjun; Li, Ting; Liao, Wenbo; Xin, Zhijun (Frontiers in Immunology, 2025)
HECT domain and ankyrin repeat-containing E3 ubiquitin-protein ligase 1 (HACE1) is a well-known tumor suppressor and is essential for embryonic development. In recent years, researchers have increasingly discovered that HACE1 plays a vital role in the pathological process of many degenerative diseases. HACE1 is regarded as a stress-responsive gene whose expression is induced by a variety of stress stimuli. The expression of HACE1 counters cell stress damage by promoting the expression of antioxidant genes and inhibiting ROS production from Rac1-dependent NADPH oxidase. Meanwhile, HACE1 serves as a crucial E3 ubiquitin ligase that activates autophagy by ubiquitinating autophagy-related receptors to clear irreversibly oxidized biomolecules within the cell. Therefore, HACE1 is essential for cellular survival by maintaining antioxidant defense mechanisms and autophagic flux. Pharmacological and genetic modulation of HACE1 expression holds potential therapeutic value in age-related diseases such as neurodegenerative disorders, cardiovascular diseases, and cancer.